Vrednotenje predpisovanja intravenske kemoterapije gastroonkološkim bolnikom - Dobravc Verbič, Matej (Farmacevtski vestnik, 2015)
Treatment of cancer is a difficult and long-lasting process that demands good collaboration of a multidisciplinary team. Cancer patients are generally older and have comorbidities, cancer chemotherapy agents are administered intravenously and have a narrow therapeutic index. Therefore, the correct prescribing of chemotherapy is extremely important. The aim of this retrospective study was to determine conformity of the chemotherapy prescribed at the Ambulatory care unit for gastrointestinal cancer patients at the Department of Gastroenterology of University Medical Centre Ljubljana with chemotherapy regimens established in international guidelines before and after clinical pharmacist's integration, which included a review of the commonly prescribed chemotherapy protocols, preparation of all protocol algorithms in use with dosing instructions, systematic check-up of chemotherapy order forms based on the prepared protocol algorithms, and performing interventions - making contact with the physician in case of any doubt or discrepancies. After clinical pharmacist's integration and performed interventions the rate of discrepant chemotherapy order forms lowered from 61.1% to 40.1%, (p < 0.001); a significant impact was seen in rates of order forms with discrepant dates (lowered from 40.3% to 24.9%, p = 0,001) and orderforms with prescribed discrepant drug dosages (lowered from 28.9 % to 2.3%, p < 0.001). Based on the results we concluded that integration of clinical pharmacist in the treatment of gastrointestinal cancer patients significantly improved the conformity of prescribing of intravenous chemotherapy with international guidelines.
Keywords: Kemoterapija; Citostatiki; predpisovanje zdravil; napake; onkologija; klinični farmacevt; farmacevtska intervencija